Personality and conceptions of religiosity across the world's religions - Baranski, E.; Kekecs, Z. ; 0000-0001-9247-9781; Arlinghaus, N.; Johnson, D.P.; O'Donnell, A.K.; Funder, D. (Journal of Research in Personality, 2024)
Research assessing personality traits and religiosity across cultures has typically neglected variation across religious affiliations and has been limited to a small number of personality traits. This study examines the relationship between the Big Five personality traits and their facets, two theoretically distinct measures of religiosity, and twelve other personality traits across seven religious affiliations and 61 countries/regions. The proportion of participants following a religion varied substantially across countries (e.g., Indonesia = 99%; Estonia = 7%). Both measures of religiosity were related to agreeableness, conscientiousness, happiness, and fairness; however; relations with religiosity as a social axiom were stronger and less variable across religious affiliations. Additionally, personality-religiosity links were more robust in low-development, high-conflict, and collectivist nations. © 2024 Elsevier Inc.
Keywords: Country variation; Personality traits; Religiosity; Religious affiliations